Pengaruh Kompetensi Sumber Daya Manusia, Kompetensi Manajerial, Dan Akuntabilitas, Terhadap Pencegahan Fraud Dana Desa Dengan Partisipasi Masyarakat Sebagai Variabel Moderating (Studi Kasus Di Kabupaten Padang Pariaman) - Nur, Aryanto (CV. ITTC INDONESIA, 2023)
This study aims to test and analyze empirically about whether Human Resource Competence (HR), Managerial Competence, Accountability have an effect on Village Fund fraud prevention, Community Participation can moderate the relationship between Human Resource Competence, Managerial Competence, Accountability and Village Fund fraud prevention . The research target population is the Village Fund fraud prevention and the variables that influence it in Padang Pariaman Regency. The number of samples is 39 nagari in Padang Pariaman Regency, with 100 respondents, the sample technique is nonprobability sampling. This research is quantitative descriptive. The data used in this research is primary data. Data collection was carried out online or offline using a questionnaire form. The analysis tool used is Smart Partial Least Square (PLS). The results of the study show that Human Resource Competence, Managerial Competence have no effect on the prevention of Village Fund fraud. Accountability influences the prevention of Village Fund fraud. Community Participation cannot strengthen and influence the relationship between Human Resource Competence, Managerial Competence, Accountability and Village Fund fraud prevention. The theoretical implications of the research strengthen existing theories, pragmatically village officials must be obliged to prevent Village Fund fraud, which has a detrimental impact on state finances. For this reason, village officials must improve Human Resource Competence, Managerial Competence, and Accountability regularly/periodically, and include Community Participation.